Reinforcement of Denture Base Resins - T Nejatiant; J Van Noortr (Tehran University of Medical Sciences, 2005)
Introduction: PMMA has been the most popular denture base material because of its advantages including good aesthetics, accurate fit, stability in the oral environment, easy laboratory and clinical manipulation and inexpensive equipments since the 1930's. However, its fracture resistance is not satisfactory. Aim: The aim of this study is to improve the fracture resistance of denture bases made of PMMA by assessing the effect of resin type, packing and processing variables on biaxial flexural strength (BFS). Materials & methods: 930 discs, 12 mm diameter and 2 mm thick were prepared with the following variables: a. Veined (V) and Plain (P) PMMA. b. 5 different powder/liquid ratios by volume (1.5:1, 2:1, 2.5:1, 3:1, 3.5:1). c. Conventional (C) and Injection packing methods (I). d. Dry heat (D) Water bath (W); and e. different curing times. The discs were trimmed and stored in 37°C tap water for 50 hours before carrying out BFS test, according to BS EN ISO 1567: 2001. BFS test was carried out using a tensile-testing machine (Lloyd LRX, Lloyd instruments Ltd) (Figure.1 b), with a x-head speed of 1mm/min. ONE-WAY ANOVA analysis and TUKEY'S comparison were carried out (MINITAB). The temperature within the curing baths and inside of curing resin was evaluated by using a thermocouple. Results: BFS of Powder/liquid ratio of 1.5:1 is significantly lower than the other four ratios. Among the last four ratios, 2.5:1 was the strongest one although the difference was not significant. BFS of the plain type of PMMA is significantly higher than the veined type.• BFS of conventionally packed PMMA discs was greater than the injectional packed ones and the difference is significant. Water bath cured resin showed a significant higher BFS compared with dry heat curing. • Changing the curing time in the dry heat bath from 7h @ 75º C and 2hrs @ 95º C to 5hrs @ 75º C and 3hrs @ 95º C and then 2hrs @ 95º C improves BFS of PMMA. In the water bath the trend is identical although the difference is not significant. Analysis of the temperature climb and hold within the curing bathes showed a consistent performance with the water bath irrespective the number of the flasks being cured. Meanwhile, the dry heat bath showed very inconsistent results. Conclusion: 1. Type of resin, packing procedure and processing variables can have major effect on BFS of PMMA. 2. Using plain resin, conventional packing, water bath curing with two hours at 95 ºC are recommended conditions.